Introducing Old Testament theology : creation, covenant, and prophecy in the divine-human relationship - Bellinger, W. H. (William H.), Jr., 1949- (Grand Rapids, Michigan : : Baker Academic, 2022)
"A senior scholar and teacher offers a concise, student-level theology of the Old Testament"--
1. Beginnings -- 2. A shape for Old Testament theology -- 3. Pentateuch -- 4. Historical books -- 5. Psalms -- 6. Wisdom -- 7. Prophecy.
Includes bibliographical references (pages 181-187) and indexes.
Keywords: Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Bible; Theology..; Criticism, interpretation, etc..